The Relationship Between Knowledge and Behavior Toward Antibiotic Stewardship Among Healthcare Workers at Referral Hospital, West Borneo - Fahira Amanda Fitaloka; Mardhia Mardhia; Mahyarudin Mahyarudin; Hariyanto IH; Delima Fajar Liana (Sanata Dharma University, 2025)
Irrational use of antibiotics is currently still a major health problem in the world. Worldwide around 50% of medicines are sold, distributed, and given to patients inappropriately. Irrational use of antibiotics can trigger antibiotic resistance. Knowledge and behavior regarding antibiotic stewardship are important in preventing antibiotic resistance. This cross-sectional research was conducted to determine the relationship between knowledge and behavior regarding antibiotic stewardship among healthcare workers. This study's 58 respondents were general practitioners/dentists, specialist doctors/dentists, and pharmacists. The instrument used in this study was a valid and reliable questionnaire. The data analysis used was univariate analysis and Spearman analysis with IBM SPSS Statistics 26 and significance set as p0.05. In this study, the results showed that the majority of respondents worked as specialist doctors/dentists (53.44%), aged in the range 26-35 years (36.20%), of the type female (58.62%), have work experience for more than 10 years (39.65%) and all of the surveyed respondents have good knowledge and behavior (100%). Spearman’s rank analysis showed no significant relationship between knowledge and antibiotic stewardship behavior (p0.05). The high level of expertise of respondents does not significantly affect the level of behavior because it can influence several factors, both internal and external. Further study is needed to identify other factors influencing antibiotic stewardship and rational use of medicine.